Systems engineering handbook: tailored for use by the USNA Small Satellite Program - Gregory, John, author; Sega, Ronald, author; Bradley, Thomas, author; Kang, Jin, author (Colorado State University. Libraries, 2023)
This handbook is adapted from the NASA Systems Engineering Handbook Rev 2: NASA/SP-2016-6105 REV 2 and specifically tailored for use in the United States Naval Academy’s Small Satellite Program. It is about a third of the size of the original NASA publication and it is specifically aimed at covering the most consequential systems engineering processes to increase the likelihood of success of undergraduate capstone teams endeavoring to conduct Small Satellite development projects with limited schedule, budget, and personnel resources.
Authors supplied by Thomas Bradley. John Gregory, Ronald Sega, and Thomas Bradley are associated with the Department of Systems Engineering, Colorado State University. John Gregory and Jin Kang are associated with the Aerospace Engineering Department, United States Naval Academy.
Keywords: CubeSats; engineering education; model-based systems engineering (MBSE); systems engineering (SE)